Ecofriendly synthesis of colorants - Cerrón-Infantes, D. Alonso (2018)
Organic colorants are an important type of compounds mainly characterized by the presence of conjugated moieties and color-generating functions (chromophores), such as carbonyl, azo or nitroso functions. They find various applications in coloring all kinds of substances – from plastics to clothes – but are unfortunately often synthesized by toxic and environmentally harmful routes. This review first explains the physicochemical basis of colorants, then gives an introduction to their classifications and general syntheses and ends with a highlight of recent advances in the environmentally friendly hydrothermal synthesis of colorants.